2021
DOI: 10.1186/s13006-021-00380-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of qualitative research on barriers and facilitators to exclusive breastfeeding practice in sub-Saharan African countries

Abstract: Background Studies reporting factors associated with exclusive breastfeeding are mostly quantitative. No study has performed a systematic qualitative summary to document the recurring constraints and facilitators to exclusive breastfeeding in sub-Saharan African countries from breastfeeding mothers’ perspective. This study systematically reviews the literature reporting barriers and facilitators to exclusive breastfeeding from the breastfeeding mothers’ perspective in sub-Saharan Africa to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 42 publications
1
39
0
1
Order By: Relevance
“…This finding is similar to a study done in Somali [ 10 ]. Moreover, a systematic review of qualitative studies from Sub-Saharan Africa also identified maternal employment as the major barrier to EBF [ 11 ]. One of the reasons could be inadequate maternity leave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is similar to a study done in Somali [ 10 ]. Moreover, a systematic review of qualitative studies from Sub-Saharan Africa also identified maternal employment as the major barrier to EBF [ 11 ]. One of the reasons could be inadequate maternity leave.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized control trial from Pakistan showed that mothers who were counseled antenatally were significantly more likely to initiate breastfeeding early and continue EBF for six months [ 19 ]. Similarly, the systematic review from Sub-Saharan Africa demonstrated that knowledge of the benefits of EBF was the most common facilitator towards EBF [ 11 ]. Therefore, other factors such as postnatal lactation support may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reviews have discovered and categorized various facilitators and barriers that affect the sustainability of interventions (55,61,63,66,67) utilizing different frameworks such as Stirman's influences on sustainability (innovation, organizational context, capacity, and processes) (61), Mays's General Theory of Implementation (capability, capacity, contribution, and potential) (68), Lennox's Consolidated Framework for Sustainability Constructs in Healthcare (initiative design and delivery, negotiating initiative processes, the people involved, resources, organizational setting, and external environment) (69), and Schell's nine domain framework (political support, funding stability, partnerships, organizational capacity, program evaluation, program adaption, communications, public health impacts, and strategic planning) (70). Moreover, few reviews identified facilitators and barriers of breastfeeding interventions (71,72), but we are unaware of any that particularly assessed those combined, relating to the sustainability of breastfeeding interventions. We categorized facilitators and barriers of interventions in this review by Scheirer and Dearing's factors affecting sustainability (intervention characteristics, organizational setting factors, and community environmental factors) (34), of which other reviews have utilized as well but in different aspects such as youth peer health education network in primary schools (73) and in a school-based bullying prevention program (74).…”
Section: Discussionmentioning
confidence: 99%
“…The health seeking behaviour is related to lack of awareness of infection as Pap smear is the only procedure of detecting cancer of the cervix. The study 16 conducted in sub-Saharan Africa revealed lack of awareness of the disease. The literature 17 indicated that lack of awareness of the diseases, perceptions and cultural beliefs also hinders respondent's practises towards cancer of the cervix screening through Pap smear.…”
Section: Discussionmentioning
confidence: 99%